Influence of Oil-Multinational Companies Educational Intervention on Quality Delivery of Education for Secondary Schools in Ondo State, Nigeria - Isiaka, Abdulaziz (Journal of Educational Sciences, 2022)
This study adopted descriptive study, four research questions were formulated and one hypothesis was postulated. Ten schools were purposively sampled, in each school ten students and five teachers were randomly selected making one hundred and fifty respondents. The findings of the study showed that 76.0% and 11.0% of the students described as very true and true. The Oil multi-national companies’ educational intervention contributes to the quality delivery of education for students in Ondo State secondary schools with the score of 8.0% and 5.0% of students also indicated untrue and very untrue. The findings showed that, 65.0% and 25.0% of the students described as very strong and strong that students are participating in the opportunities provided by oil multi- national companies for secondary schools in Ondo state while 4.0% and 6.0% described as poor and very poor. This study gave the following recommendations: Government should show a great concern towards the educational wellbeing of students as this would foster sponsors to support the government in educating students, Secondary school management should ensure a proper platform not necessarily an online platform for the awareness of opportunities provided by oil multinational companies to secondary schools to aid quality delivery of western education.